Չորք-Մարզուանի ուխտավայրերի անուան եւ գտնուելու վայրերի շուրջ - Վերա Սահակեան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
The province Chker is one of the settlements in Cilician Armenia where there are a lot of churches. Chork-Marzvan being one of the provinces populated with Armenians, had numerous churches and monasteries, which have never been as a subject of research. In the XIX century many of these sanctuaries were in ruins, and became pilgrimages. Провинция «Чкэр» - богатое церквями селение, находящееся на территории Киликийской Армении. Один из районов провинции, «Чорк-Марзван», имеющий густое армянское население, известен своими многочисленными церквями и монастырями, которые никогда не становились предметом изучения. В 19 веке большая часть этих святынь уже стала руинами и считалась местом паломничества.
Keywords: Christianity; History of the Armenian Church